PENGARUH RUANG KONSELING YANG IDEAL DAN KETERAMPILAN MENDENGARKAN KONSELOR TERHADAP KETERBUKAAN DIRI KONSELI - Lasmi Bekstari, Dewi Putri (Educatio Vitae, 2014)
Counseling ideal space is a space that is used for the purpose of providing assistance to students / counsele who are facing problems , especially in the implementation of individual counseling a completed equipment supplies and funny. So that Guidance and counseling services in order to run effective and efficient so for needed support facility and infrastructure for confidentiali counseling problem society. So that counsele to bring a problem for counselor not openly that for with here counselor must be have listening skill with good and smart. If the counselor listen with right so counselor to feel the counselor is attention and helpened. The determination of this research to know counseling space ideal effect and listening skill counselor to self disclosure counsele. The population in this research is students of class XI SMA 3 Madiun 2013/2014 with the number of 211 person-8 class. The sampling technicue by author of Cluster Sampling . Data received with using angket metode type in scale -shaped space counseling ideal , listening skills counselor and selfdisclosure counsele. In this research the authors to propose three hypotheses : 1 ) space counseling ideal the effect for self-disclosure counsele 2 ) Listening skills counselor the effect for selfdisclosure counselee , 3 ) space counseling ideal and listening skills counselor the effect for self-disclosure counsele. The data pals analisys with double linear regression tehnic . with referency result of data process can be as following : 1 ) Model of regressi line equality Y = -1.648 +0.271 ( X1 ) + 0.370 ( X2 ) . 2 ) Correlation anality to have strong effect with number R totaly 0.632 . 3 ) Determination coeficien totaly 0.400 , this problem is the ideal counseling space and listening skills counselor totaly 40% to the plan of self-disclosure counsele . 4 ) Hypothesis " counseling space ideal the effect for self-disclosure counselee " , received . 5 ) Hypothesis " Listening skills counselor the effect for self-disclosure counsele " , received . 6 ) Hypothesis " counseling space ideal and listening skills counselor the effect for self-disclosure counsele " , received .